Silicon-carbon negative electrode material for lithium battery and production method thereof
By preparing silicon-carbon composite materials with porous structures and optimized binders, the problem of powdering and shedding caused by volume expansion of silicon anode materials in lithium batteries is solved, the rate performance and cycle stability are improved, and the safety of the battery is improved performance and service life.
Patent Information
- Application Number
- CN202411063338.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-08-05
AI Technical Summary
During the charging and discharging process of lithium batteries, the volume expansion of the silicon negative electrode material leads to powdering and falling off, affecting the rate performance and cycle stability; at the same time, excessive amount of adhesive can easily cause the pores of porous carbon material to be blocked, increasing safety hazards.
Silicon-carbon composite materials are used to form porous carbon materials through modified cyclodextrin gel carbonization, and silicon is deposited through chemical vapor deposition to form silicon-carbon composite materials with a large specific surface area. At the same time, an adhesive prepared by free radical polymerization of liquid styrene-butadiene rubber and eugenol is used to reduce the amount of adhesive and enhance the bonding strength.
It effectively limits the stress changes caused by the volume expansion of the silicon particle layer, improves the rate performance and cycle stability of the lithium battery, and reduces the risk of the adhesive blocking the pores of the porous carbon material, improving the safety and service life of the battery. .
Smart Images

Figure CN118825238B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of negative electrode materials for lithium batteries, and in particular to a silicon-carbon negative electrode material for lithium batteries and a production method thereof. Background Art
[0002] With the rapid development of the new energy industry, lithium batteries have gradually attracted the attention of researchers due to their environmental protection, low self-discharge rate and no memory effect. As the application scope of lithium batteries becomes wider and wider, traditional lithium batteries use graphene as the negative electrode material of the battery, and its low theoretical capacity has been difficult to meet people's demand for lithium batteries. Correspondingly, silicon-based negative electrode materials have emerged. Silicon-based negative electrode materials have high theoretical specific capacity. Silicon-based lithium batteries have extremely high energy density, which can provide longer battery life. However, during the battery charging and discharging process, the silicon negative electrode material undergoes a huge volume expansion when lithium is inserted and shrinks when lithium is removed, forming a large stress change. , which can easily lead to pulverization of the negative electrode material, thereby causing rapid attenuation of the battery capacity and affecting the rate performance and cycle stability of the lithium battery. If the bonding strength between the negative electrode material and the current collector is insufficient, it may even cause the negative electrode material to fall off directly when the lithium battery is working. In order to avoid such problems, the amount of adhesive is usually increased in the negative electrode material to increase the bonding area and enhance the bonding strength between the negative electrode material and the current collector. However, excessive use of adhesive has the risk of clogging the pores of the porous carbon material, resulting in insufficient pores when the volume of the silicon material deposited in the porous carbon expands. Large stress changes can easily cause the porous carbon material to collapse, posing a safety hazard.
[0003] In order to solve this problem, a commonly used method is to compound silicon and carbon materials to form a silicon-carbon composite material, and to coat silicon with carbon materials to limit the intensity of silicon volume change, thereby alleviating the stress change and improving the cycle stability of lithium batteries. For example, the patent with publication number CN108598430B discloses a method for preparing a silicon-carbon negative electrode material and a porous carbon microsphere negative electrode material. Silicon-carbon microspheres are prepared, and then the porous silicon-carbon microsphere negative electrode material is obtained after carbonization and etching, so that it can maintain a high capacity retention rate after multiple cycles; the patent with publication number CN114597377B discloses a silicon-carbon composite negative electrode material, a negative electrode and a lithium secondary battery, in which the surface of the silicon material is coated with a silane binder, and amorphous carbon, the silane binder and the conductive carbon material are bonded so that the prepared negative electrode material can maintain a constant porosity range, thereby improving the energy density and cycle life of the battery. Summary of the invention
[0004] The purpose of the present invention is to provide a silicon-carbon negative electrode material for lithium batteries and a production method thereof, which solves the following technical problems: (1) During the charging and discharging process of lithium batteries, the volume expansion of silicon negative electrode materials can easily lead to pulverization and shedding of the negative electrode materials, thereby causing the lithium battery rate to decrease and the capacity to decay rapidly; (2) The excessive amount of binder in the negative electrode material of lithium batteries can easily cause pore blockage of porous carbon materials.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A silicon-carbon negative electrode material for a lithium battery is obtained by mixing a conductive agent, a silicon-carbon composite material, an adhesive and deionized water to form a slurry; the conductive agent is any one of carbon black, graphene and carbon nanotubes; the silicon-carbon composite material is formed by carbonizing a modified cyclodextrin gel to form a porous carbon material, and then subjected to silicon deposition treatment; the adhesive is obtained by free radical polymerization of liquid styrene-butadiene rubber and eugenol.
[0007] Furthermore, the method for preparing the silicon-carbon composite material comprises the following steps:
[0008] S1: Place cyclodextrin in deionized water, heat to 50-55°C, stir thoroughly for 1-2h, add nitrilotriacetic acid and catalyst, continue stirring for 5-8h, let stand for 12-24h, and freeze-dry at -55 to -45°C for 10-15h to obtain modified cyclodextrin gel;
[0009] S2: The modified cyclodextrin gel and ammonium chloride are fully mixed, placed in a porcelain boat, nitrogen is introduced, heated to 550-600°C in a tube furnace, kept warm for 30-50 minutes, and then cooled to room temperature, washed, dried, and ground to obtain a porous carbon material;
[0010] S3: Using chemical vapor deposition, the porous carbon material is placed in a tubular furnace, silane and hydrogen are introduced, and the temperature is increased to obtain a silicon-carbon composite material after silicon deposition treatment.
[0011] Through the above scheme, under the action of a catalyst, the hydroxyl groups in the cyclodextrin structure and the multiple carboxyl groups in the nitrilotriacetic acid structure undergo an esterification reaction to form a cross-linked network structure, and a modified cyclodextrin gel is obtained after freeze-drying. Under the action of a porogen, the modified cyclodextrin gel is carbonized to form a porous carbon material with uniform and abundant pores. Silicon is deposited in the porous carbon material structure by chemical vapor deposition to form a silicon-carbon composite material. The silicon-carbon composite material uses porous carbon as a matrix, which can provide a larger specific surface area, thereby combining more lithium ions, improving the specific capacity of lithium batteries, and promoting the electron The transmission of silicon in the electrode material improves the rate performance of the battery. The silicon particle layer deposited on the porous carbon can be nanometer-sized, which can reduce the absolute volume of the silicon particles, reduce the particle pulverization problem caused by volume expansion, and significantly improve the specific capacity of the battery. At the same time, the porous carbon skeleton can limit the change in strength caused by the volume expansion of silicon, alleviate the stress change caused by the volume expansion of silicon, and improve the service life of the lithium battery. In addition, nitrogen is doped in the silicon-carbon composite material, which can introduce additional electrons and improve the electrical conductivity of the material, thereby enhancing the diffusion rate of lithium ions, significantly improving the rate performance, specific capacity and cycle stability of the lithium battery.
[0012] Furthermore, in step S1, the catalyst is p-toluenesulfonic acid.
[0013] Furthermore, in step S2, the heating rate in the tube furnace is 10-15°C / min.
[0014] Furthermore, in step S3, the temperature rise silicon precipitation treatment is to rise to 600-650° C. and process for 15-25 minutes.
[0015] Furthermore, the preparation method of the adhesive is:
[0016] Place liquid styrene-butadiene rubber in a torque rheometer, set the temperature to 130-145°C and the speed to 80-90r / min, add eugenol, styrene and initiator, and plasticize for 5-8 minutes before discharging. Add toluene to dissolve, and then remove the solvent by rotary evaporation to obtain an adhesive.
[0017] Through the above technical scheme, under the action of the initiator, the unsaturated double bonds in the structure of liquid styrene butadiene rubber and the unsaturated double bonds in the structure of eugenol undergo free radical polymerization reaction to obtain an adhesive. The liquid styrene butadiene rubber has certain bonding properties. After polymerization with eugenol, a large number of phenolic hydroxyl groups are introduced into its molecular chain, which can significantly enhance its bonding strength. When used as an adhesive in the negative electrode material of a lithium battery, only a small amount is needed to tightly bond the silicon-carbon composite material, the conductive agent and the negative electrode current collector. Reducing the amount of adhesive does not reduce the bonding strength, and can prevent the clogging of the pores of the porous carbon material caused by excessive addition of adhesive, thereby excessively limiting the space required for the volume expansion of the silicon material, resulting in the stress change generated when the silicon material expands directly acting on the porous carbon skeleton. Too little buffer space is likely to cause the porous carbon skeleton to collapse, affecting the cycle stability of the lithium battery. It also has great safety hazards and affects the service life of the lithium battery.
[0018] Furthermore, the initiator is any one of benzoyl peroxide and dicumyl peroxide.
[0019] A method for producing a silicon-carbon negative electrode material for a lithium battery, the production method comprising the following steps:
[0020] The silicon-carbon composite material, the conductive agent, the adhesive and deionized water are mixed to form a slurry to obtain a silicon-carbon negative electrode material for a lithium battery.
[0021] Furthermore, the mass ratio of the silicon-carbon composite material, the conductive agent, and the adhesive is 7-8:1-1.5:0.3-0.5.
[0022] Beneficial effects of the present invention:
[0023] The present invention prepares a silicon-carbon composite material and an adhesive and adds the adhesive to the production process of the silicon-carbon negative electrode material for the lithium battery. During the charge and discharge process of the lithium battery, the stress change caused by the volume expansion of the silicon particle layer can be limited, and the rate performance and cycle stability of the lithium battery can be improved. At the same time, the amount of adhesive can be reduced without reducing the bonding strength between the silicon-carbon composite material, the conductive agent and the negative electrode collector, thereby preventing the clogging of the pores in the silicon-carbon composite material due to excessive adhesive. The silicon-carbon composite material can have more pores, better alleviate the stress changes caused by the volume expansion of the silicon material, and improve the safety and service life of the lithium battery.
[0024] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0026] Figure 1 is a SEM image of the modified cyclodextrin gel in Example 1 of the present invention;
[0027] Figure 2 The SEM images and TEM images of the silicon-carbon composite material in Example 2 of the present invention; a is the SEM image of the silicon-carbon composite material, and b is the TEM image of the silicon-carbon composite material;
[0028] Figure 3 This is the infrared spectrum of liquid styrene-butadiene rubber and adhesive in Example 3 of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] Preparation of modified cyclodextrin gel
[0032] 10 g of cyclodextrin was placed in 100 ml of deionized water, heated to 50°C, and stirred for 1 h. 5 g of nitrilotriacetic acid and 1 g of p-toluenesulfonic acid were added, and the mixture was stirred for 5 h. After standing for 12 h, the mixture was freeze-dried at -55°C for 10 h to obtain a modified cyclodextrin gel.
[0033] The Flash Smart element analyzer was used to test the nitrogen content in cyclodextrin and modified cyclodextrin gel. The test showed that cyclodextrin does not contain nitrogen, and the nitrogen content in the modified cyclodextrin gel is 2.2%. This is because the hydroxyl group in the cyclodextrin structure reacts with nitrilotriacetic acid, introducing nitrogen into the modified cyclodextrin gel.
[0034] Figure 1 This is the SEM image of the modified cyclodextrin gel. It can be seen from the figure that the modified cyclodextrin gel has a cross-linked network structure because multiple hydroxyl groups in the cyclodextrin structure and multiple carboxyl groups in the nitrilotriacetic acid structure undergo a cross-linking reaction to form a three-dimensional network structure.
[0035] Example 2
[0036] Preparation of Silicon Carbon Composite Materials
[0037] S1: 10 g of modified cyclodextrin gel and 1 g of ammonium chloride were fully mixed, placed in a porcelain boat, introduced with nitrogen, heated to 550 °C at a rate of 10 °C / min in a tube furnace, kept warm for 30 min, cooled to room temperature, washed, dried, and ground to obtain a porous carbon material;
[0038] S2: Using chemical vapor deposition, the porous carbon material is placed in a tubular furnace, silane and hydrogen are introduced, the temperature is raised to 600°C, and silicon precipitation treatment is performed for 15 minutes to obtain a silicon-carbon composite material.
[0039] Figure 2 The SEM and TEM images of the silicon-carbon composite material, wherein a is the SEM image of the silicon-carbon composite material, and b is the TEM image of the silicon-carbon composite material. It can be seen from a that the silicon-carbon composite material has a porous structure. This is because the modified cyclodextrin hydrogel has a cross-linked network structure. The added ammonium chloride will decompose at high temperature to produce gas, which will etch it, thus forming a silicon-carbon composite material with a porous structure. It can be seen from b that the silicon material in the silicon-carbon composite material is coated with carbon material, which effectively solves the problem of volume expansion of the silicon material during the charging and discharging process of the lithium battery.
[0040] With reference to standard SJ / T11792-2022, the conductivity of silicon-carbon composite materials and commercially available silicon-carbon composite materials were tested. The commercially available silicon-carbon composite materials were purchased from Shanghai Shanshan Technology Co., Ltd. The specific test results are shown in the table below:
[0041]
[0042]
[0043] It can be seen from the above table that the electrical conductivity of the silicon-carbon composite material prepared by the present invention is higher than that of the commercially available silicon-carbon composite material. This is because the silicon-carbon composite material prepared by the present invention is doped with nitrogen, and carbon is deposited after silicon is deposited in the porous carbon, which establishes a tighter conductive network, increases the transmission efficiency of electrons, and thus enhances the conductivity of the silicon-carbon composite material.
[0044] Example 3
[0045] Preparation of adhesive
[0046] Place 5 ml of liquid styrene-butadiene rubber in a torque rheometer, set the temperature to 130°C and the speed to 80 r / min, add 3 g of eugenol, 1 g of styrene and 0.6 g of initiator, and plasticize for 5-8 minutes before discharging the material. Add 20 ml of toluene to dissolve it, and then remove the solvent by rotary evaporation to obtain an adhesive.
[0047] Using a Fourier infrared spectrometer, the liquid styrene-butadiene rubber and adhesive were mixed and ground with potassium bromide, sliced, and tested for infrared spectrum. The test spectrum range was 4000-500cm -1 ,Depend on Figure 3 It can be seen that in the infrared spectrum of liquid styrene-butadiene rubber, 3023cm -1 The absorption peak of the carbon-hydrogen bond in the benzene ring is 3065cm -1 The absorption peak of the carbon-hydrogen bond in the olefin group is at 3256cm -1 The absorption peak of hydroxyl is at 3023cm -1 The absorption peak of the carbon-hydrogen bond in the benzene ring is 1065cm -1 The absorption peak of the carbon-oxygen bond in the ether bond is at the center, and the absorption peak of the carbon-hydrogen bond in the olefin group basically disappears, indicating that the double bonds in the structure of liquid styrene-butadiene rubber and the double bonds in the structure of eugenol have undergone free radical polymerization.
[0048] The peel strength test was conducted on the adhesive and the commercially available styrene-butadiene rubber adhesive according to the reference standard GB / T2792-2014. The styrene-butadiene rubber adhesive was purchased from Jinan Shouyue Chemical Technology Co., Ltd. The specific test results are shown in the following table:
[0049] Peel strength (N / mm) Adhesives 0.25 Commercially available styrene butadiene rubber adhesive 0.14
[0050] It can be seen from the above table that compared with commercially available styrene butadiene rubber adhesives, the adhesive prepared by the present invention has higher peel strength. This is because the present invention introduces multiple phenolic hydroxyl groups into the liquid styrene butadiene rubber structure, which can enhance the bonding strength of the liquid styrene butadiene rubber, so that the prepared adhesive has excellent peel strength.
[0051] Example 4
[0052] Preparation of silicon-carbon negative electrode materials for lithium batteries
[0053] A silicon-carbon composite material, a conductive agent carbon black, and a binder in a mass ratio of 7:1:0.3 were placed in 30 ml of deionized water, and stirred evenly at room temperature to form a viscous slurry to obtain a silicon-carbon negative electrode material for a lithium battery.
[0054] Comparative Example 1
[0055] Preparation of silicon-carbon negative electrode materials for lithium batteries
[0056] A commercially available silicon-carbon composite material, a conductive agent carbon black, and a binder prepared in Example 3 of the present invention in a mass ratio of 7:1:0.3 were placed in 30 ml of deionized water, and stirred evenly at room temperature to form a viscous slurry to obtain a silicon-carbon negative electrode material for a lithium battery.
[0057] Comparative Example 2
[0058] Preparation of silicon-carbon negative electrode materials for lithium batteries
[0059] The silicon-carbon composite material prepared in Example 2 of the present invention, conductive agent carbon black, and commercially available styrene-butadiene rubber binder in a mass ratio of 7:1:0.3 were placed in 30 ml of deionized water and stirred evenly at room temperature to form a viscous slurry to obtain a silicon-carbon negative electrode material for a lithium battery.
[0060] Comparative Example 3
[0061] A commercially available silicon-carbon composite material, a conductive agent carbon black, and a commercially available styrene-butadiene rubber binder in a mass ratio of 7:1:0.3 were placed in 30 ml of deionized water, stirred evenly at room temperature to form a viscous slurry, and a silicon-carbon negative electrode material for a lithium battery was obtained.
[0062] Performance Testing
[0063] ① The silicon-carbon negative electrode material for lithium batteries prepared in Example 4 and Comparative Examples 1 to 3 was coated on a copper foil electrode current collector, dried and sintered in a vacuum furnace, and then cooled to room temperature, cut into silicon-carbon electrodes that meet the specifications, and used metal lithium foil as a counter electrode. A Celgard 2500 diaphragm and a KLD-1376 electrolyte were used to assemble a 2032-type button half-cell in an argon-filled super-purified glove box for testing; after the assembled button half-cell was left for 10 hours, a 1.0 A / g constant current charge and discharge cycle test was performed in a voltage range of 0.1-1.5 V. The specific test results are shown in the following table:
[0064] Specific capacity (mAh / g) Capacity retention after 100 cycles (%) Example 4 1782 93.2 Comparative Example 1 1005 74.6 Comparative Example 2 1521 89.3 Comparative Example 3 765 69.4
[0065] As can be seen from the above table, the lithium battery assembled by using the silicon-carbon negative electrode material prepared in Example 4 to make the negative electrode sheet has excellent specific capacity, and can still have a capacity retention rate of 93.2% after 100 cycles. The silicon-carbon negative electrode material prepared in Comparative Example 1 uses a commercially available silicon-carbon composite material and an adhesive prepared in Example 3 of the present invention. The lithium battery assembled by using this negative electrode material to make the negative electrode sheet has a general specific capacity. After 100 cycles, the capacity retention rate is only 74.6%. The silicon-carbon negative electrode material prepared in Comparative Example 2 uses the adhesive prepared in Example 3 of the present invention. The silicon-carbon composite material prepared in Example 2 and the commercially available styrene-butadiene rubber binder are used to make a lithium battery assembled with a negative electrode sheet, and the specific capacity reaches 1521 mAh / g. After 100 cycles, it can still have a capacity retention rate of 89.3%. The silicon-carbon negative electrode material prepared in Comparative Example 3 uses a commercially available silicon-carbon composite material and a commercially available styrene-butadiene rubber binder, has a low specific capacity, and the capacity retention rate decays too quickly after 100 cycles, and has poor stability. This shows that the silicon-carbon composite material and adhesive prepared by the present invention have a promoting effect on the cycle stability of the lithium battery.
[0066] ② The silicon-carbon negative electrode materials prepared in Example 4 and Comparative Examples 1 to 3 were used to make electrode sheets, which were assembled into lithium batteries as samples. The rate performance of the samples was tested with reference to the standard GB / T18287-2013. The rate charging performance investigated the constant current charging ratio of 3C charging, and the rate discharge performance mainly investigated the capacity retention rate of 3C discharge. The test results are shown in the following table:
[0067] Constant current charging ratio (%) Capacity retention rate (%) Example 4 92.2 97.3 Comparative Example 1 72.6 86.8 Comparative Example 2 90.4 92.6 Comparative Example 3 65.8 79.3
[0068] It can be seen from the above table that the sample in Example 4 has excellent rate performance. The sample assembled in Comparative Example 1 uses a commercially available silicon-carbon composite material and an adhesive prepared in Example 3 of the present invention, and has a general rate performance. The sample assembled in Comparative Example 2 uses a silicon-carbon composite material prepared in Example 2 of the present invention and a commercially available styrene-butadiene rubber adhesive, and has excellent rate performance. The sample assembled in Comparative Example 3 uses a commercially available silicon-carbon composite material and a commercially available styrene-butadiene rubber adhesive, and has a poor rate performance. This indicates that the silicon-carbon negative electrode material made of the silicon-carbon composite material and the adhesive prepared by the present invention has a more excellent rate performance after being made into an electrode sheet and assembled into a lithium battery.
[0069] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0070] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A silicon-carbon negative electrode material for lithium batteries, characterized in that: The conductive agent, silicon-carbon composite material, adhesive and deionized water are mixed to form a slurry; the conductive agent is any one of carbon black, graphene and carbon nanotubes; the silicon-carbon composite material is a porous carbon material formed by carbonizing modified cyclodextrin gel and then depositing silicon; the adhesive is prepared by free radical polymerization of liquid styrene-butadiene rubber and eugenol; The preparation method of the silicon-carbon composite material comprises the following steps: S1: placing cyclodextrin in deionized water, heating to 50-55°C, stirring for 1-2h, adding nitrilotriacetic acid and a catalyst, stirring for 5-8h, standing for 12-24h, and freeze-drying at -55 to -45°C for 10-15h to obtain a modified cyclodextrin gel; S2: The modified cyclodextrin gel and ammonium chloride are fully mixed, placed in a porcelain boat, nitrogen is introduced, heated to 550-600° C. in a tube furnace, kept warm for 30-50 min, then cooled to room temperature, washed, dried, and ground to obtain a porous carbon material; S3: Using chemical vapor deposition, the porous carbon material is placed in a tubular furnace, silane and hydrogen are introduced, and the temperature is increased to obtain a silicon-carbon composite material after silicon precipitation treatment.
2. A silicon-carbon negative electrode material for lithium battery according to claim 1, characterized in that: In step S1, the catalyst is p-toluenesulfonic acid.
3. A silicon-carbon negative electrode material for lithium battery according to claim 1, characterized in that: In step S2, the heating rate in the tube furnace is 10-15°C / min.
4. The silicon-carbon negative electrode material for lithium battery according to claim 1, characterized in that: In step S3, the temperature of the silicon deposition treatment is raised to 600-650° C. for 15-25 minutes.
5. The silicon-carbon negative electrode material for lithium battery according to claim 1, characterized in that: The preparation method of the adhesive is: Place liquid styrene-butadiene rubber in a torque rheometer, set the temperature to 130-145°C and the speed to 80-90r / min, add eugenol, styrene and initiator, and plasticize for 5-8 minutes before discharging. Add toluene to dissolve, and then remove the solvent by rotary evaporation to obtain an adhesive.
6. A silicon-carbon negative electrode material for lithium battery according to claim 5, characterized in that: The initiator is any one of benzoyl peroxide and dicumyl peroxide.
7. A method for producing a silicon-carbon negative electrode material for a lithium battery as claimed in claim 1, characterized in that: The production method comprises the following steps: The silicon-carbon composite material, the conductive agent, the adhesive and deionized water are mixed to form a slurry to obtain a silicon-carbon negative electrode material for a lithium battery.
8. The method for producing a silicon-carbon negative electrode for a lithium battery according to claim 7, characterized in that: The mass ratio of the silicon-carbon composite material, the conductive agent and the adhesive is 7-8:1-1.5:0.3-0.5.
Citation Information
Patent Citations
Preparation method of silicon-carbon anode material and porous silicon-carbon microsphere anode material
CN108598430B
A silicon-carbon composite anode material, an anode, and a lithium secondary battery
CN114597377B
Silicon-carbon negative electrode material taking cyclodextrin and derivatives thereof as pore-forming agent and preparation method
CN111640941A
Silicon oxide negative electrode material and preparation method thereof
CN115148986A